Anticholinergic Exposure in a Cohort of Adults Aged 80 years and Over: Associations of the MARANTE Scale with Mortality and Hospitalization. Issue 6 (6th April 2017) - Wauters, Maarten; Klamer, Therese; Elseviers, Monique; Vaes, Bert; Dalleur, Olivia; Degryse, Jan; Durán, Carlos; Christiaens, Thierry; Azermai, Majda; Vander Stichele, Robert
Abstract: Anticholinergics are frequently prescribed for older adults and can lead to adverse drug events. The novel MARANTE (Muscarinic Acetylcholinergic Receptor ANTagonist Exposure) scale measures the anticholinergic exposure by incorporating potency and dosages of each medication into its calculations. The aims were to assess prevalence and intensity of the anticholinergic exposure in a longitudinal cohort study of community‐dwelling patients aged 80 years and over (n = 503) and to study the impact on mortality and hospitalization. Chronic medication use at baseline (November 2008–September 2009) was entered and codified with the Anatomical Therapeutic Chemical classification. Time‐to‐event analysis until first hospitalization or death was performed at 18 months after inclusion, using Kaplan–Meier curves. Cox regression was performed to control for covariates. Mean age was 84 years (range 80–102), and mean number of medications was 5 (range 0–16). Prevalence of anticholinergic use was 31.8%, with 9% taking ≥2 anticholinergics (range 0–4). Main indications for anticholinergics were depression, pain and gastric dysfunction. Female gender, the level of multi‐morbidity and the number of medications were associated with anticholinergic use. Mortality and hospitalization rate were 8.9% and 31.0%, respectively. After adjustment for the level of multi‐morbidity and medication intake, multi‐variable analysis showed increased risks of mortality (HR 2.3, 95% CI: 1.07–4.78) and hospitalization (HR 1.7; 95% CI: 1.13–2.59) in those with high anticholinergic exposure. The longitudinal study among Belgian community‐dwelling oldest old demonstrated great anticholinergic exposure, which was associated with increased risk of mortality and hospitalization after 18 months.